2008
DOI: 10.2514/1.32650
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open and Choked Premixed Combustor Exits During Thermoacoustic Limit Cycle

Abstract: This paper compares the thermoacoustic limit cycles of a premixed laboratory combustor with acoustically open and choked exits. It is shown that the form of the downstream boundary condition can have a significant effect on the combustion chamber acoustics, with both the dominant limit cycle frequencies and the acoustic mode shapes being very different for the different combustor exits. The fundamental limit cycle frequency with the choked exit in place agrees closely with that determined by the convective tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…MacQuisten and Dowling [40] reported a strong low-frequency instability in their combustor when the exit was choked, and speculated that this was the cause. Hield and Brear [42] also observed a similar low-frequency instability, and showed experimentally that the conversion of incident entropy disturbances to upstream travelling sound can be significant.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…MacQuisten and Dowling [40] reported a strong low-frequency instability in their combustor when the exit was choked, and speculated that this was the cause. Hield and Brear [42] also observed a similar low-frequency instability, and showed experimentally that the conversion of incident entropy disturbances to upstream travelling sound can be significant.…”
Section: Introductionmentioning
confidence: 74%
“…Whilst thermoacoustic instability has been studied extensively in premixed combustors over the last few decades, most studies have concentrated on combustors with acoustically open exits. The effect of a choked exit nozzle has received less attention [40][41][42]. This is an important omission, given that some of those studies that have been carried out suggest that a choked exit nozzle can have a strong effect on the system stability [3,40,42,43], and that most in service combustors feature a choked, or nearly choked, nozzle downstream of the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The time delay between the PMT and hot-wire signals was calculated using a cross correlation Method [11,37]. The phase of the flame transfer function was then defined as ϕ = 2πfτ where τ (s) is the heat release time delay relative to the upstream velocity forcing [17,38].…”
Section: Post Processing Of the Experimental Datamentioning
confidence: 99%
“…Further, the essential physics of thermoacoustic instabilities are not entirely understood [6,7]. This is mostly due to the complexities involved in the interactions between premixed flames and sound waves [9,10] and, to some extent, the effects of system boundaries [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There is now a body of experimental [21,22] and theoretical [23,24,11] works showing that entropy noise could influence the thermoacoustic instability of laboratory scale combustors. Yet, the studies conducted in real engines revealed much less effects [25,26].…”
Section: Introductionmentioning
confidence: 99%